Formation of Bicyclic Cyclopentenone Derivatives by Robinson-Type Annulation of Cyclic β-Oxoesters Containing a 1,4-Diketone Moiety - Geibel, Irina; Kahrs, Christoph; Christoffers, Jens (Synthesis, 2017)
Robinson-type cyclopentannulations of cyclic β-oxoesters possessing a 1,4-diketone moiety are accomplished under four different Brønsted basic reaction conditions. Using pyrrolidine/acetic acid in DMSO, an oxohexahydrocyclopenta[a]indene (42%) and an N-Boc-protected oxohexahydrocyclopenta[c]pyridine derivative (62%) are obtained with retention of the ester moieties. The latter compound defines an interesting new scaffold for medicinal chemistry with three positions allowing further derivatizations. The use of KOtBu in DMSO or NaH in toluene leads to cyclopentene derivatives with either partial ester saponification and decarboxylation or displacement of the ester moiety within the carbon skeleton. With aqueous KOH, the cyclopentannulations are successful in almost all cases, but with the ester moieties cleaved off. The respective bicyclic and tricyclic products are obtained in good to excellent yields. The 1,4-diketone starting materials are prepared by cerium-catalyzed oxidative coupling of β-oxoesters with isopropenyl acetate. Alternatively, a two-step sequence consisting of α-propargylation followed by palladium-catalyzed alkyne hydration is used.
Keywords: heterocyclic compounds; piperidine derivatives; cyclopentenone; Robinson annulation; ketones; diketones; alicyclic compounds; bicyclic compounds; alkyne hydration